The role of sustainable growth rate in mediating liquidity, profitability, and company size on financial performance - Erawati, Teguh; Kusuma, Hadri; Stefania Dai Suban; Fuadhillah Kirana Putri (Jurnal Akuntansi dan Auditing Indonesia, 2025)
Financial performance has a very strategic importance for the company. This study aims to examine the effect of liquidity, profitability and company size on Sustainable Growth Rate, and the effect of the Sustainable Growth Rate on financial performance for companies. The data used in this study were taken from companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This study uses purposive sampling method to obtain relevant samples resulting in a total of 2365 company observations. The results showed that liquidity has a negative effect on the Sustainable Growth Rate, while profitability and company size have a positive effect on Sustainable Growth Rate. While the Sustainable Growth Rate has a positive effect on financial performance, indicating that companies with higher SGR tend to have better financial performance. The results of the study have important implications for management, namely, to increase profitability as an effort to encourage higher SGR, which in turn can improve overall financial performance. This study indicates that companies with high SGR levels may be a more stable investment option, given the positive impact of SGR on financial performance.